Niger : 2013 First Review Under the Three-Year Arrangement Under the Extended Credit facility and Request for a Waiver of Nonobservance of Performance Criterion-Staff Report; Staff Supplements; and Press Release. (IMF Staff Country Reports; Country Report, 2013)
Economic activity was buoyant in Niger thanks to a new oil project, contributing to a strengthened external account and a rebound in agricultural production. Economic developments, however, remained vulnerable to climatic shocks and the fragile security situation in the region. Fiscal developments were affected by shortfalls in oil and customs revenue credit to the private sector. The government budget has been made with the objective of maintaining macroeconomic stability while advancing development. The implementation of the financial sector development strategy and poverty reduction strategy is required.